Hubungan Antara Loneliness dengan Parasocial Relationship pada Mahasiswa Penggemar K-Pop - Hartika Utami Fitri; Manah Rasmanah; Shona Tuzzahra (DA'WA: Jurnal Bimbingan Penyuluhan & Konseling Islam, 2025)
Students are vulnerable to experiencing loneliness. Students with high psychosocial pressure such as loneliness and depression tend to be more comfortable interacting socially online than in-person social activities and one of them makes parasocial relationships an alternative. This study looked at how much of a relationship between the level of loneliness and parasocial relationships in K-Pop fan students. The sample from this study amounted to 159 respondents and the sampling technique was in the form of purposive sampling. Data were collected by questionnaire. In measuring loneliness variables, the De Jong Gierveld Loneliness Scale (DJGLS) was adapted. Meanwhile, parasocial relationships are measured by adapting the Celebrity Attitude Scale (CAS) created by Maltby, et al. The results of the study showed that students who were interested in K-pop had a moderate level of loneliness (80%) and a moderate level of parasocial relationship (73%). By using Pearson Product Moment, a significant value of 0.00 and greater than 0.05 (0.00> 0.05) was obtained so that there was a relationship between Loneliness and Parasocial Relationship in K-Pop Fan Students.